PENGARUH MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN BAGIAN PRODUKSI PADA PT. LIMA PUTRA CONTRINDO CIKANDE-SERANG - Zahra, Surti; Pratiwi, Ika; Ismiyati, Ismiyati (Gapenas Publisher, 2024)
Employee performance is one of the things that can make a company develop or not, work motivation and work discipline are factors that can affect employee performance. The aim is to determine the effect of work motivation and work discipline on the performance of production employees at PT. Lima Putra Contrindo Cikande-Serang either partially or simultaneously. This research method uses associative quantitative methods with non-probability sampling methods with a population of 120 respondents while a sample of 55 respondents is calculated from the slovin formula, and this research was processed using the SPSS Version 26 application. The results of this study stated that (H1) the significance value was 0.013 <0.05 and the tcount> ttable or 2.568 > 1.674 then Ha was accepted and Ho was rejected (H2) the significance value was 0.010 <0.05 and the tcount> ttable or 6.030 > 1.674 then Ha is accepted and Ho is rejected (H3) significance value is 0.000 <0.05 and Fcount > Ftable, (41,565 > 3.18) then Ha is accepted and Ho is rejected. The conclusion in this study can be concluded that (H1) There is an influence between the independent variables of motivation on employee performance (H2) There is an influence between the independent variables of work discipline on employee performance (H3) There is an influence between the independent variables of work motivation and work discipline on employee performance